2*1/(x^2+3*x*y)+3*1/(y^2-x*y)=25/14 3*1/(x^2+3*x*y)-2*1/(y^2-x*y)=-4/7

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Решение

Вы ввели
[LaTeX]
    2           3       25
---------- + -------- = --
 2            2         14
x  + 3*x*y   y  - x*y     
$$\frac{3}{- x y + y^{2}} + \frac{2}{x^{2} + 3 x y} = \frac{25}{14}$$
    3           2           
---------- - -------- = -4/7
 2            2             
x  + 3*x*y   y  - x*y       
$$- \frac{2}{- x y + y^{2}} + \frac{3}{x^{2} + 3 x y} = - \frac{4}{7}$$
Быстрый ответ
[LaTeX]
$$x_{1} = - \frac{7}{2}$$
=
$$- \frac{7}{2}$$
=
-3.5

$$y_{1} = \frac{1}{2}$$
=
$$\frac{1}{2}$$
=
0.5
$$x_{2} = -1$$
=
$$-1$$
=
-1

$$y_{2} = -2$$
=
$$-2$$
=
-2
$$x_{3} = 1$$
=
$$1$$
=
1

$$y_{3} = 2$$
=
$$2$$
=
2
$$x_{4} = \frac{7}{2}$$
=
$$\frac{7}{2}$$
=
3.5

$$y_{4} = - \frac{1}{2}$$
=
$$- \frac{1}{2}$$
=
-0.5
Численный ответ
[LaTeX]
x1 = 3.50000000000000
y1 = -0.500000000000000
x2 = 0.9999999999999999
y2 = 2.00000000000000
x3 = -3.50000000000000
y3 = 0.500000000000000